Prevalence of type 2 diabetes mellitus and its associated factors among a public university staff in Selangor - B., Prem Kumar; Kadir@Shahar, Hayati; Gyanchand Rampal, Lekhraj Rampal (Community Health Society Malaysia, 2014)
Background: Type 2 diabetes mellitus is a common non-communicable disease worldwide. The prevalence of type 2 diabetes mellitus in Malaysia is increasing trend. The aim of this study was to determine the prevalence, associated factors and the predictors of type 2 diabetes mellitus among University Putra Malaysia staff. Materials and Methods: A cross sectional study was conducted between May 2014 to June 2014 among 189 staff aged 30 years and above, at University Putra Malaysia, Serdang. The probability proportional to size sampling technique was used to recruit both academic and non-academic staff for this study. A pre tested bilingual self-administered questionnaire was used to collect data on socio-demographic, family history, medical comorbidities and lifestyle factors. Height, weight, waist and hip circumference and blood pressure were measured. Blood samples were taken to analyse HbA1c level. Results: A total of 189 respondents were recruited and the response rate was 82.5%. The overall prevalence of type 2 diabetes mellitus was 12.8%. There was an association between prevalence of type 2 diabetes mellitus and age, gender and history of hypertension and hyperlipidaemia, physical activity, smoking status, alcohol consumption and obesity. The predictors of having type 2 diabetes mellitus were smoking status (AOR=4.84; 95%CI: 1.54- 15.22; P=0.007), hypertension (AOR=3.89; 95%CI:1.19-12.75; P=0.025) and hyperlipidaemia (AOR=4.00; 95%CI:1.27-12.67; P=0.018). Conclusions: The prevalence of type 2 diabetes mellitus among University Putra Malaysia staff was low compared to national prevalence in 2011 and was associated with age, gender, physical activity, smoking status, alcohol consumption, obesity, history of hypertension and hyperlipidaemia. The predictors of type 2 diabetes mellitus were smoking status, hypertension and hyperlipidaemia. Health promotions and screenings for type 2 diabetes mellitus is recommended.